The Effect Of Shallot Compress On Reducing Body Temperature In Babies With Fever At PMB Wanti Medan - Sembiring, Elya Rosa Br; Damanik, Syahroni; Siahaan, May Frinsiska; Marlina, Marlina; Marfuah, Marfuah (Universitas Prima Indonesia, 2025)
According to the Medan City Health Office in 2022, out of 7 Health Centers in Medan City, the highest number of children visiting for fever was 1,994 children. Fever can be treated non-pharmacologically by compressing red onions because red onions contain organic sulfur compounds, namely Allycysteine ​​sulfoxide (Alliin). The purpose of this study was to determine the effect of red onion compresses on reducing body temperature in babies with fever at PMB Wanti in 2025. The design of this study is Quasi Experiment with one group pre test post test. The population is10respondents and samples using accidental sampling, namely 10 respondents. The data used using primary and secondary data. Data analysis using univariate and bivariate using non-parametric with sample T test. The results of the study showed that there was an effect of red onion compresses on reducing the body temperature of babies with fever at PMB Wanti.Year 2025with a p value of 0.000<0.05. Conclusion: There is an effect of red onion compresses on reducing the body temperature of babies with fever at PMB Wanti.Year 2025.It is expected that health workers, especially midwives at PMB, will provide education and knowledge to mothers who have babies so that they can provide red compresses as initial treatment for children with fever.